Pengaruh Metode Outdoor Learning dengan Berbantuan Media “UTAKA” dalam Peningkatan Keterampilan Kognitif Siswa Sekolah Dasar - Dita Wahyu Rivaningtyas; Dwi Cahyono Dewo; Eka Marintasari; Elma Firmanasari; Elvi Marsiani; Erlynda Runtut Bela Vista; Ika Krisdiana (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
This research is a quantitative research using experimental methods. This research was motivated by the problem of low cognitive knowledge of grade IV students at SDN 02 Klegen Madiun City. This study aims to determine the effect of the application of UTAKA's media-assisted outdoor learning method in cognitive improvement of science subject students of natural appearance material in grade IV students of SDN 02 Klegen Madiun in the even semester of the 2023/2023 academic year. The data analysis techniques used are normality tests, homogeneity tests, and research hypothesis tests using t tests. The results of the distribution normality test through the Shapiro-Wilk test obtained a significance value of the experimental group of 0.437 and the control group of 0.566. The results of the calculation of the variance homogeneity test through the Levene test obtained a significance value of 0.172. The value is said to be homogeneous because the significance value of the experimental group and the control group >0.05. The results of hypothesis testing obtained Sig. (2-tailed) values of 0.001 < 0.05. So it can be concluded that there is an influence on the application of UTAKA media-assisted outdoor learning methods in cognitive improvement of science subject students of natural appearance material in grade IV students of SDN 02 Klegen Madiun City.